Investigating Factors Influencing Consumer Willingness to Buy GM Food and Nano-food - Yue, Chengyan (2015)
Emerging technologies applied to food products often evoke controversy about their safety and whether to label foods resulting from their use. As such, it is important to understand the factors that influence consumer desires for labeling and their willingness-to-buy (WTB) these food products. Using data from a national survey with US consumers, this study employs structural equation modeling to explore relationships between potential influences such as trust in government to manage technologies, views on restrictive government policies, perceptions about risks and benefits, and preferences for labeling on consumer’s WTB genetically modified (GM) and nano-food products. Some interesting similarities and differences between GM- and nano-food emerged. For both technologies, trust in governing agencies to manage technologies did not influence labeling preferences, but it did influence attitudes about the food technologies themselves. Attitudes toward the two technologies, as measured by risk–benefit comparisons and comfort with consumption, also greatly influenced views of government restrictive policies, labeling preferences, and WTB GM or nano-food products. For differences, labeling preferences were found to influence WTB nano-foods, but not WTB GM foods. Gender and religiosity also had varying effects on WTB and labeling preferences: while gender and religiosity influenced labeling preferences and WTB for GM foods, they did not have a significant influence for nano-foods. We propose some reasons for these differences, such as greater media attention and other heuristics such as value-based concerns about “modifying life” with GM foods. The results of this study can help to inform policies and communication about the application of these new technologies in food products.